Effects of the combination of anti-PcrV antibody and bacteriophage therapy in a mouse model of Pseudomonas aeruginosa pneumonia - Ohara Junya; Fujiki Jumpei; Mao Kinoshita; Kazuki Sudo; Ken Kawaguchi; Keita Inoue; Yoshifumi Naito; Kiyoshi Moriyama; Tomohiro Nakamura; Hidetomo Iwano; Teiji Sawa (Microbiology Spectrum)
ABSTRACT Acute lung injury caused by Pseudomonas aeruginosa is attributed to the translocation of cytotoxin into pulmonary epithelial cells via the P. aeruginosa type III secretion system. This virulence can be blocked with a specific antibody against PcrV in this secretion system. However, because anti-PcrV antibodies do not have bactericidal activity, the treatment of bacteria depends on the phagocytic system of the host. In this study, we investigated the therapeutic effect of combination therapy with an anti-PcrV antibody and bactericidal bacteriophages on acute lung injury and subsequent death in mice compared with a single treatment. After the mice intratracheally received a lethal dose of the cytotoxic P. aeruginosa strain, a second instillation was performed with saline, anti-PcrV IgG, bacteriophages, or a mixture of anti-PcrV and bacteriophages. The survival rates 24 h after infection were as follows: 7.1% in the saline group, 26.7% in the anti-PcrV group, 41.2% in the phage group, and 66.7% in the anti-PcrV + phage group (P < 0.001 vs saline-treated group). The activity of surviving mice in the anti-PcrV + phage group was significantly greater than that in the saline group. The lung weight in the anti-PcrV + phage group was significantly lower than that in the anti-PcrV group. In conclusion, combination therapy with an anti-PcrV antibody and a bacteriophage reduces acute lung injury and suggests improved survival compared with each treatment alone. This combination therapy, which does not rely on conventional antibiotics, could constitute a new strategy for treating multidrug-resistant P. aeruginosa infections.IMPORTANCECombination therapy with either bacteriophages alone or in combination with anti-PcrV antibodies in a mouse model of Pseudomonas aeruginosa pneumonia may reduce the acute lung injury and improve survival. This combination therapy, which does not rely on conventional antibiotics, may be a new strategy to treat multidrug-resistant Pseudomonas aeruginosa infections.